Impact of general data protection regulation on children's rights in digital environment - Krivokapić Đorđe; Adamović Jelena (Anali Pravnog Fakulteta u Beogradu, 2016)
Raising the age of consent to data processing to 16 and allowing member states to set it at a lower age, was one of the major points of argument in the wake of passing the new EU General Data Protection Regulation (GDPR), otherwise hailed for introducing the Article 8 that recognizes children as a vulnerable group. This paper analyzes legal grounds for concerns raised over the provisions related to personal data protection of minors, possible ramifications and remedies within the given framework. It also highlights innovations and positive solutions set in the GDPR, with respect to privacy risks and opportunities for children in the information society.